Hybrid magnetic Irish moss/Fe3O4 as a nano-biocatalyst for synthesis of imidazopyrimidine derivatives. Issue 56 (24th May 2016) - Hemmati, Behnaz; Javanshir, Shahrzad; Dolatkhah, Zahra
Abstract : A new magnetically separable Fe3 O4 @IM nano-biocatalyst was synthesized using natural Irish moss (IM) and its catalytic activity was studied in the synthesis of imidazopyrimidine derivatives. Abstract : Irish moss (IM), derived from the Chondrus crispus is a family of sulphated polysaccharide that are extracted from certain kinds of algae (red edible seaweeds). In this study, new magnetically separable, recoverable Fe3 O4 nanoparticles were synthesized in the presence of natural Irish moss (IM) to afford Fe3 O4 @IM. FT-IR analysis, scanning electron microscopy (SEM), transmission electron microscopy (TEM), VSM analysis, Energy-Dispersive X-ray Spectroscopy (EDX) and X-ray diffraction (XRD) were combined for the characterization of the Fe3 O4 @IM nanocomposite. Afterward, the first catalytic report of Fe3 O4 @IM with no post-modification was achieved by studying its catalytic activity in the synthesis of imidazopyrimidine derivatives via a three-component reaction of 2-aminobenzimidazole, aldehyde, and C–H acidic compounds under reflux in ethanol. 1 H nuclear overhauser effect (NOE) experiments have been used to ascertain the regioselectivity of addition and condensation reactions. Based on this study, Fe3 O4 @IM is an efficient, magnetically separable, recyclable, and green catalyst.